2014
DOI: 10.1002/hbm.22488
|View full text |Cite
|
Sign up to set email alerts
|

White matter development and early cognition in babies and toddlers

Abstract: The normal myelination of neuronal axons is essential to neurodevelopment, allowing fast inter-neuronal communication. The most dynamic period of myelination occurs in the first few years of life, in concert with a dramatic increase in cognitive abilities. How these processes relate, however, is still unclear. Here we aimed to use a data-driven technique to parcellate developing white matter into regions with consistent white matter growth trajectories and investigate how these regions related to cognitive dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 72 publications
7
137
0
Order By: Relevance
“…This may be because the bulk of myelination has occurred by age 1 y and individual variation in cognitive development in the second year of life is less dependent on further maturation of myelin and more dependent on inherent structure reflected in AD. This notion is supported by a previous study that found only a very weak association of MWF, a myelin-related imaging parameter, with Mullen cognitive scores in young children (16). In addition, a similar study found MWF had more widespread correlations with ECL in 1-to 2-y-olds compared with 2-to 4.8-y-olds (15).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This may be because the bulk of myelination has occurred by age 1 y and individual variation in cognitive development in the second year of life is less dependent on further maturation of myelin and more dependent on inherent structure reflected in AD. This notion is supported by a previous study that found only a very weak association of MWF, a myelin-related imaging parameter, with Mullen cognitive scores in young children (16). In addition, a similar study found MWF had more widespread correlations with ECL in 1-to 2-y-olds compared with 2-to 4.8-y-olds (15).…”
Section: Discussionsupporting
confidence: 69%
“…Two recent studies found that myelination, as measured by myelin water fraction (MWF), is predictive of general cognitive ability in young children (15,16). However, little is known about how intertract microstructural covariance develops in this period of rapid growth, and how it is related to cognitive development.…”
mentioning
confidence: 99%
“…Myelination is thus assumed to improve the functional efficiency of brain networks (van der Knaap et al, 1991). As examples, expressive and receptive language abilities during toddlerhood are related to the myelin water fraction in the white matter underlying the frontal and temporal cortices (O'Muircheartaigh et al, 2014), and visuospatial working memory performance at 1 year of age correlates with microstructural characteristics of white matter tracts that connect involved brain regions (Short et al, 2013).…”
Section: Functional Correlates Of White Matter Myelinationmentioning
confidence: 99%
“…Particularly, the first two years of life may be key for the development of the EA network. A rapid exponential myelination growth takes place over frontal areas about the 6th month of life [38]. Cortical grey volume also increases substantially in the first two years of life, with a faster growth of frontal structures during the second year of age [39,40].…”
Section: Early Development Of the Ea Networkmentioning
confidence: 99%